Influence of Crystallization Temperature on Structural, Ferroelectric, and Ferromagnetic Properties of Lead-Free Bi0.5(Na0.8K0.2)0.5TiO3 Multiferroic Films - Ngo Duc Quan; Tran Quoc Toan; Vu Ngoc Hung; Minh-Duc Nguyen (Advances in Materials Science and Engineering, 2019)
Lead-free Bi0.5(Na0.8K0.2)0.5TiO3 (abbreviated as BNKT) films have been synthesized via a sol-gel technique on Pt/Ti/SiO2/Si substrates, and the dependence of the physical properties in BNKT films were investigated as a function of the crystallization temperature. The BNKT films were annealed at different temperatures (600, 650, 700, and 750°C) for 60 min in the air. The results of this study showed that the optimal crystallization temperature is 700°C. At this, the BNKT films exhibited a single perovskite phase structure and high-dense surface. Besides, the remanent (Pr) and maximum (Pm) polarization reached their highest values of 9.2 µC/cm2 and 30.6 µC/cm2, respectively. All the films showed a weak ferromagnetic behavior with the maximum saturated magnetization (Ms) of 2.1 emu/cm3. These values are equivalent to the highest Pr and Pm values in previous reports on lead-free films.